SQL All-in-One For Dummies - Taylor, Allen G. (Wiley Publishing, 2011)
SQL, or structured query language, is the international standard language for creating and maintaining relational databases. It is the basis of all major databases in use today and is essential for the storage and retrieval of database information. This fun and friendly guide takes SQL and all its related topics and breaks it down into easily digestible pieces for you to understand. You’ll get the goods on relational database design, development, and maintenance, enabling you to start working with SQL right away!